Analisis Kekuatan Rangka Mesin Pencacah Nilam dengan Menggunakan Metode Elemen Hingga - Nanang Endriatno; La Ode Ahmad Barata; Salimin (Piston: Jurnal Teknologi, 2024)
Frames are often used as essential elements in the construction of machines and various other engineering products. The strength of the frame is significant in ensuring that the structure can withstand operational loads when used. Frame failure can cause severe damage, accidents, and substantial financial losses, so evaluating the strength of the frame before production is a critical step in the design process. This study aims to analyze the mechanical behavior of the components or frames of the patchouli chopping machine based on the maximum stress, displacement, and safety factor of the designed frame. The research method using finite element simulation technology is an efficient approach to analyzing the performance of frame structures. By utilizing simulations, a comprehensive evaluation of various parameters such as stress, displacement, and frame safety can be carried out. This process helps predict the structure's response to multiple loads received by the system. The simulation results using the finite element method show that the L-profile frame 40x40x3 mm with a cross-sectional area of ​​307.863 mm2 can withstand a maximum load of 1000 N with a maximum deformation of 0.2479 mm, which occurs at the load center. The von Mises stress distribution shows that the stress that occurs in the L-profile steel is 28.8 MPa. This value is far below the material yield strength threshold of 207 MPa. The maximum Safety Factor value that occurs in the frame is 15 ul, and there is no safety factor value below 1. The simulation results show that the analyzed frame is safe and meets the specified design requirements